Billing Barber Shop (An Implementation of GoodBarber App Builder) - Upik Sri Sulistyawati; Bahruni; Afrizal; Alfina (Lembaga Komunitas Informasi Teknologi Aceh (KITA), 2022)
The research objective is to develop a Billing Barbershop application by implementing GoodBarber App Builder in application development. The research method used in this study consists of 5 parts, namely the literature study method, data collection method, analysis method, design method, and the development method used is extreme programming. From the research results, a Billing Barber Shop application has been developed by implementing the GoodBarber App Builder which is designed to consist of login, home, billing, orders, product, and users forms. The test results are known in Usability testing, Compatibility testing, Interface testing, Low level resource, Performance testing, Operational testing, Installation testing, and Security testing stating very good with an average percentage above 80%. But in Service testing, choosing poor because Billing Barber Shop still uses the internet as a connection to data using Zapier Add-ons and Google Sheets.